Respuesta :
Answer:
a=4 , b=-9
Step-by-step explanation:
p(x) = 4x^4 + ax^3 + bx^2 -x +2 = (2x^2 - x - 1) q(x)
q(x) = cx^2 + dx + e
then we want to figure out the values of c, d and e
for c, 2x^2 * cx^2 = 4x^2, c=2
for e, -1 * e = 2, e = -2
for d, dx*(-1) + (-x) * e = -x, -dx + 2x = -x, d = 3
so,
q(x) = 2x^2 + 3x -2
to get the value of a and b, we just have to expand
(2x^2 - x - 1) (2x^2 + 3x -2)
that is,
4x^4 + 6x^3 - 4x^2 - 2x^3 - 3x^2 + 2x - 2x^2 - 3x +2
simplify it,
p(x) = 4x^4 + 4x^3 - 9x^2 - x + 2
so a = 4 and b = -9
Answer:
a = 4 b = -9
Step-by-step explanation:
2x² – X – 1 = (2x+1)(x-1) 2 roots: 1 and -1/2
if x=1: 4x⁴ + ax³ + bx² – x + 2 = 4(1)⁴+a(1)³+b(1)²-1+2 = 0
a + b + 5 = 0 ...(1)
if x = 1/2 4(1/2)⁴+a(1/2)³+b(1/2)²-1/2+2 = 0
14/8 + a/8 + b/4 = 0 ... times 8 both side
a + 2b + 14 = 0 ..(2)
(2) - (1): b + 9 = 0 b = -9
a = 4
check: 4x⁴ + 4x³ -9x² – x + 2 = (2 x - 1) (2 x + 1) (x - 1) (x + 2)
= (2x² - x - 1) (2x² +x - 2)